Introducing Life Skills Through Project-Based Learning in Speaking for Informal Communication Course - Ridwan Yasin Setiawan; Diani Nurhajati (EDUCATIO : Journal of Education, 2025)
In industrial revolution era 4.0, students should be equipped with life skills. The skills must be introduced to students in all level, including higher education level. There are many strategies to train those skills to students, one of which is through Project-Based Learning (PjBL). The students will get various experiences through the steps of the teaching model. The aims of this research were to describe the steps of PjBL in Speaking for Informal Communication and to explain the process of acquiring life skills experienced by the students in Speaking for Informal Communication. This research used descriptive qualitative design. The subjects of the research were a lecturer who taught the subject and two students who took the subject. The techniques of data collection were observation, interviews and document analysis. The results of this research showed that the life skills obtained by the students were (1) self-awareness and personal life skills, (2) social skills, (3) thinking skills, (4) academic skills, (5) vocational skills.